Analisis Faktor-Faktor yang mempengaruhi Inflasi di Indonesia Tahun 1990-2009 - Agus Subiyanto; Sarastri Mumpuni R (Jurnal Aplikasi Bisnis, 2017)
Inflation is an economic disease that has broadly impact to the economy as a whole. Therefore inflation oftenly becomes government policy target since it is able to lead economic instability, show economic growth, and increase unemployment rate. The high level of inflation in Indonesia both in long and short term can be influenced by policies implemented by Central Bank (Bank Indonesia) as themonetaiy authority (interest rate), the the government's policy on spending (routine expense), the amount of money supply in the society, and the foreign sector (export earnings and kurs).